Gold Mineralization In The Marine Environment; A Possible Marine Mineral Exploration And Mining Target - Thomas Pichler (International Marine Minerals Society, 1993)
In the past marine mining technology has focused on bulk mining of base metals from polymetallic massive sulfides. This has not been very successful because of the relatively low unit value of these metals and other reasons such as water depth, etc.. The process of gold enrichment in hydrothermal deposits is controlled through five different factors: (1) nature and source of the solution, (2) source of the gold, (3) a mechanism for mobilizing and transporting, (4) a mechanism for deposition, and (5) a mechanism to preserve the deposit. Gold has been identified in marine polymetallic massive sulfides from various locations on the ocean floor (e.g., spreading centers, seamounts) with contents ranging up to 5 ppm Au. This is within the current range of 1.0 to 7.0 ppm gold content which classifies gold ores. The gold appears to have been derived during hydrothermal alteration of the oceanic crust. Until the present there has been little attention to the possibility of mining gold or other precious metals in the marine environment. However, the magnitude of hydrothermal alteration (seawater can penetrates to a depth of 5 km into the oceanic crust) and primary gold contents of the rocks in the pathway of the fluid indicates that major gold deposits must have formed on or in the ocean floor, but they have not been found. To find a big deposit might only take an exploration model exclusively designed for gold exploration on the ocean floor.